2015
DOI: 10.1051/0004-6361/201425262
|View full text |Cite
|
Sign up to set email alerts
|

The StEllar Counterparts of COmpact high velocity clouds (SECCO) survey

Abstract: We present an imaging survey that searches for the stellar counterparts of recently discovered ultra-compact high-velocity H  clouds (UCHVC). It has been proposed that these clouds are candidate mini-haloes in the Local Group and its surroundings within a distance range of 0.25-2.0 Mpc. Using the Large Binocular Telescope we obtained wide-field ( 23 × 23 ) g-and r-band images of the twenty-five most promising and most compact clouds amongst the fifty-nine that have been identified. Careful visual inspection o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Our detection for AGC 258242 would be well outside that footprint, assuming the LBT image is centered on the Hi centroid. In the case of AGC 268074, the object detected in our pODI images would likely fall within the LBT image footprint, but Bellazzini et al (2015) do not detect an overdensity in their data for this UCHVC.…”
Section: Overdensities With 90% < ξ < 97%mentioning
confidence: 67%
See 1 more Smart Citation
“…Our detection for AGC 258242 would be well outside that footprint, assuming the LBT image is centered on the Hi centroid. In the case of AGC 268074, the object detected in our pODI images would likely fall within the LBT image footprint, but Bellazzini et al (2015) do not detect an overdensity in their data for this UCHVC.…”
Section: Overdensities With 90% < ξ < 97%mentioning
confidence: 67%
“…While they do not meet the criteria for robust detections because of their lack of supporting overdensities, these marginal detections are still potential stellar counterparts. Two of these objects were observed by Bellazzini et al (2015), AGC 258242 and AGC 268074. Neither of these objects had significant stellar overdensities in the Large Binocular Telescope images from that work, though the footprint of those images is smaller (14 × 7 ) than that of the pODI images.…”
Section: Overdensities With 90% < ξ < 97%mentioning
confidence: 99%
“…8. The source (ID number 100038 in our catalog) is seen as extended both in the OSIRIS images and in the deep g,r images of the original SECCO survey (Bellazzini et al 2015a). It has a nearby point-like companion (100046) with significant Hα excess.…”
Section: Hα Imaging: Searching For Additional Piecesmentioning
confidence: 99%
“…Previous work has shown that stellar counterparts for UCHVCs appear to be rare and correspond to more distant, massive systems with typical H i masses of ∼ 10 7 M (Bellazzini et al 2015;Sand et al 2015). However, Janesh et al (2015) identified a tentative optical counterpart for one UCHVC, AGC 198606, at a distance of 383 kpc.…”
Section: Introductionmentioning
confidence: 95%